AN ANALYSIS OF FARMING BUSINESS AND SHALLOT EFFICIENCY IN THE SIDOMAKMUR FARMER GROUP - Rizqi Yudha Pratama; Suci Nur Utami; Muhammad Dini Adita (Universitas Muhadi Setiabudi, 2021)
Shallots are one of the strategic horticultural commodities and have high economic value. The level of public consumption of shallots in Indonesia continues to increase. The abundance of shallot production in Brebes makes shallot prices fluctuate. The abundance of harvest yields also affected the decline in the price of shallots in Brebes. This study aims to determine the Analysis of Farming Profits and Efficiency of Shallot Farming in the Sidomakmur Farmer Group, Sidamulya Village, Wanasari District, Brebes Regency, Central Java. The research method used is descriptive quantitative. In one planting period, the Sidomakmur farmer group spends a total cost of Rp. 130,000,000 and get an income of Rp. 227.900.000. So that in one planting season the Sidomakmur farmer group has a profit of Rp. 97.900.000, and based on calculations with the formula NPMx/Px = 1, the efficiency of farming is 0.82 or 82%, which means that the Sidomakmur farmer group is less efficient in running the farming business because it is still below 1. It is expected that the Sidomakmur farmer group maximizes the existing potential. so that onion farming can be efficient.